The Effect of Sharia Investment and Government Policy on the Financial Performance of MSMEs in West Java - Budi Utama, Ahmad Nur; Firdaus, Dian; Priyana, Yana (West Science Interdisciplinary Studies, 2024)
This study investigates the impact of Sharia investment and government policy on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in West Java. Utilizing a quantitative approach, data was collected from 120 MSMEs through structured questionnaires employing a Likert scale ranging from 1 to 5. The collected data was analyzed using SPSS version 26 to determine the correlation and effect of the independent variables—Sharia investment and government policy—on the dependent variable, financial performance. The findings indicate a significant positive relationship between Sharia investment and financial performance, as well as between government policy and financial performance. This suggests that both Sharia-compliant financial practices and supportive government policies play crucial roles in enhancing the financial outcomes of MSMEs in the region. The results underscore the importance of adopting Sharia investment strategies and fostering government policies that support the growth and sustainability of MSMEs.